Community Empowerment Through the Bangkit Sejahtera Forest Farmer Group in Gajahrejo Village, Gedangan District, Malang Regency - Rahayu, Sri Lestari; Rasyad, Ach; Dayati, Umi (Proceedings Series of Educational Studies, 2024)
Educational platforms and human resource development are the sole goals of forest farmer group organizations. However, based on field observations, the enormous potential of non-timber forest products is still less accessible to forest farmer groups. Forest farmers must be empowered to become independent group business managers, as evidenced by low production and minimal human resources. The first objective of this research is to explain the empowerment program offered at KTH Bangkit Sejahtera. The second objective is to describe the empowerment methods applied there. (3) Mention the challenges faced by Bangkit Sejahtera forest farmers in their efforts to gain greater authority. By using case study methodology, this research uses a qualitative research strategy. At the Bangkit Sejahtera Forest Farmers Group Institute located on Jl. The Southern Cross of Gajahrejo in Gedangan District, Malang Regency, research has been carried out. Interviews and observations were used as data collection methods. The stages of data reduction, data presentation, and drawing conclusions are used to test the data obtained. Source and time triangulation was used to verify the accuracy of the data. The research results show that by carrying out various empowerment activities and successfully completing them, the Bangkit Sejahtera Farmers Group has been able to carry out its role as a forum for learning and community development. Communities gain information, skills and improved economic conditions as a result of these empowerment initiatives. The KTH Rising Sejahtera empowerment process follows the current stages, which include planning, implementation and assessment. However, there are many obstacles faced by institutions in implementing it. Keywords: Forest Farmers Group; Empowerment